Spectrophotometric and HPLC determination of deflazacort in pharmaceutical dosage forms - Amarilis Scremin; Monika Piazzon; Marcos Antonio Segatto Silva; Gislaine Kuminek; Giane Márcia Correa; Niraldo Paulino; Simone Gonçalves Cardoso (Brazilian Journal of Pharmaceutical Sciences, 2010)
Deflazacort (DFZ) is a glucocorticoid used as an anti-inflammatory and immunosuppressant drug. No official methods are available for DFZ determination in pharmaceutical formulations. The objective of this study was to develop, validate and compare spectrophotometric (UV and colorimetric) and high-performance liquid chromatography (HPLC) methods, for the quantitative determination of DFZ in tablets and oral suspension. For the UV method, ethanol was used as the solvent, with detection at 244 nm. The colorimetric method was based on the redox reaction with blue tetrazolium in alkaline medium, with detection at 524 nm. The method by HPLC was carried out using a C18 column, mobile phase consisting of acetonitrile:water (80:20, v/v) with a flow rate of 1.0 mL min-1 and detection at 244 nm. The methods proved linear (r > 0.999), precise (RSD < 5%) and accurate (recovery > 97%). Statistical analysis of the results indicated that the UV and HPLC methods were statistically equivalent, while the values obtained for the colorimetric method differed significantly from the other methods. O deflazacorte (DFZ) é um fármaco glicocorticóide usado como antiinflamatório e imunossupressor. Métodos oficiais não estão disponíveis para a determinação de DFZ em formas farmacêuticas. Este estudo teve como objetivo desenvolver, validar e comparar métodos por espectrofotometria (UV e colorimetria) e cromatografia líquida de alta eficiência (CLAE), na determinação quantitativa de DFZ em comprimidos e suspensão oral. O método por UV utilizou etanol como solvente, com detecção em 244 nm. O método colorimétrico foi baseado na reação de redução com azul de tetrazólio em meio alcalino, com detecção em 524 nm. O método por CLAE utilizou coluna C18; fase móvel constituída de acetonitrila:água (80:20, v/v), com fluxo de 1,0 mL min-1 e detecção em 244 nm. Os métodos foram lineares (r > 0,999); precisos (RSD < 5 %), e exatos (recuperação > 97%). As análises estatísticas dos resultados obtidos indicaram que os métodos por UV e por CLAE foram estatisticamente equivalentes, enquanto os valores obtidos para o método colorimétrico diferiram significativamente dos demais métodos.